2019
DOI: 10.1007/s10877-019-00351-7
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of pocket-sized ultrasound devices in measurement of optic nerve sheath diameter in ICU patients

Abstract: The measurement of the optic nerve sheath diameter (ONSD) by ultrasonography (USG) is particularly important for intracranial pressure (ICP) monitoring when invasive measurements are not possible or are contraindicated. Standard USG (SUDs) devices can be bulky and may break down the workflow. The validity and reliability of pocket-sized USG devices (PSUDs) compared to SUDs for ONSD measurement has not been investigated, yet. We compared the reliability and validity of PSUDs with SUDs for ONSD measurement. 35 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
4
0
2
Order By: Relevance
“…15 The only previous study using ICC for inter-rater reliability of ONSD ultrasound in intensive care patients reported an ICC of 0.84 (no 95% CI reported). 16 With the excellent intra-and inter-rater results emanating from the current study, we suggest that all ONSD examinations should be standardized and based on the CLOSED protocol. Based on the nonsignificant trend favoring an increased number of measurements, we also suggest that ONSD should be measured at least twice from every angle to improve precision.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…15 The only previous study using ICC for inter-rater reliability of ONSD ultrasound in intensive care patients reported an ICC of 0.84 (no 95% CI reported). 16 With the excellent intra-and inter-rater results emanating from the current study, we suggest that all ONSD examinations should be standardized and based on the CLOSED protocol. Based on the nonsignificant trend favoring an increased number of measurements, we also suggest that ONSD should be measured at least twice from every angle to improve precision.…”
Section: Discussionmentioning
confidence: 53%
“…ICC was 0.74 (95% CI; 0.65, 0.81) for inter‐rater reliability 15 . The only previous study using ICC for inter‐rater reliability of ONSD ultrasound in intensive care patients reported an ICC of 0.84 (no 95% CI reported) 16 …”
Section: Discussionmentioning
confidence: 96%
“…Decontamination assessment must never be compromised. Some recent studies have shown that pocket-sized US performed efficiently as a tool for screening a variety of diseases[ 16 , 20 , 29 , 30 , 34 , 41 ]. The pocket-sized US devices were also used successfully by other healthcare providers, such as nurses and physical therapists.…”
Section: Use Of Pocket-sized Us Devices In Clincal Settingsmentioning
confidence: 99%
“…Ainda, possui a vantagem de fácil aprendizado, não causa complicações e pode ser aplicado à beira leito por médicos emergencistas e intensivistas. Todavia, ainda não existem recomendações específicas sobre o seu uso (PANSELL et al, 2023;ÖZDEMIR et al, 2019).…”
Section: Introductionunclassified